The internationalization strategies of wine cooperatives of Portugal : the cases of Borba, Vermelha, S. Mamede da Ventosa and S. Isidro de Pegões - Simões, Diogo António Rodrigues (2018)
The present dissertation deals with internationalization strategies from 3 wine cooperatives of Portugal and the national strategy of one of the most notorious wine cooperative of the country with the purpose of demonstrate the importance and potential that these kind of companies have in the present economy. The central research questions are: “Can wine cooperatives be as competitive and successful as private companies?” and “Does the cooperative structure affect the internationalization process and the way managers run the company?” With these in mind, the opinion of 4 managers was heard in order to verify if in fact any constraints or limitations are felt and if anything would be done differently in a corporate context. Furthermore, the challenges to internationalization and the success factors needed are discussed. The study concludes that the problem of cooperatives goes beyond its structure. Cooperatives need to be managed with a private company mentality in order to keep up with the market. Also, professional management, competitiveness by the members and alignment by all the stakeholders are a must in order that the business can prosper and conflicts of interest do not happen. In addition to that, the cooperatives managers consider the image of Portugal in international markets and the brutal competition the main challenges.